1965
DOI: 10.1152/ajplegacy.1965.208.6.1129
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal distribution of ammonia during diuresis and antidiuresis

Abstract: The intrarenal distribution of ammonia was evaluated in the dog during antidiuresis and osmotic (mannitol) diuresis at various levels of urine pH. During antidiuresis, the concentration of ammonia in renal tissue water rose progressively from the cortex to the tip of the papilla. In contrast, the corticomedullary ammonia gradient was completely obliterated by osmotic diuresis. In both experimental groups, a close relationship was observed between urine pH and the logarithm of the ratio between the urine and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1967
1967
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…1 20 min preceded the collection of the first urine specimen to ensure attainment of steady state conditions. The ammonia pool of the kidney is no doubt small but turns over rapidly (15). The half-time of the turnover rate estimated from pool size in the dog kidney (15) and from pool turnover in our experiments is about 1 min.…”
Section: Resultsmentioning
confidence: 48%
“…1 20 min preceded the collection of the first urine specimen to ensure attainment of steady state conditions. The ammonia pool of the kidney is no doubt small but turns over rapidly (15). The half-time of the turnover rate estimated from pool size in the dog kidney (15) and from pool turnover in our experiments is about 1 min.…”
Section: Resultsmentioning
confidence: 48%
“…Second, it has been reported that the pH of loop fluid is more alkaline than fluid obtained at end proximal micropuncture sites (1,2). Lastly, the concentration of ammonia in renal tissue increases from cortex to medulla (20,21) and ammonium formation in collecting duct fluid seems dependent on this gradient. Thus, while the concentration in cortical tissue is not altered by an osmotic diuretic the gradient from cortex to medulla disappears (20) and ammonia entry into the collecting duct is diminished (21).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally recognized that transfer of ammonia from the loops of Henle to the collecting ducts in the renal medulla is an important process facilitating renal ammonium excretion (4,(14)(15)(16). This transfer process involves reabsorption of ammonia from the loops of Henle and accumulation of ammonia to high concentrations in the medullary interstitium (4,(17)(18)(19)(20). Because secretion of ammonia by the collecting ducts depends on the NH3 concentration difference between the interstitial fluid and the collecting duct lumen (4,17,21,22), the ability of the kidney to accumulate ammonia in the medulla and maintain a high medullary interstitial NH3 concentration is an important factor in the maintenance of a high rate of total ammonia excretion.…”
Section: Role Ofmedullary Thick Ascending Limb In Ammonium Excretionmentioning
confidence: 99%
“…Because secretion of ammonia by the collecting ducts depends on the NH3 concentration difference between the interstitial fluid and the collecting duct lumen (4,17,21,22), the ability of the kidney to accumulate ammonia in the medulla and maintain a high medullary interstitial NH3 concentration is an important factor in the maintenance of a high rate of total ammonia excretion. The high ammonia content ofthe renal medulla has been proposed to depend on countercurrent multiplication (5,20,23). Direct evidence to support this possibility was provided when the thick ascending limb of Henle's loop was demonstrated to absorb NHZ against a concentration gradient (5).…”
Section: Role Ofmedullary Thick Ascending Limb In Ammonium Excretionmentioning
confidence: 99%
See 1 more Smart Citation